Epac Function and cAMP Scaffolds in the Heart and Lung - Laudette, Marion (J Cardiovasc Dev Dis, 2018)
Evidence collected over the last ten years indicates that Epac and cAMP scaffold proteins play a critical role in integrating and transducing multiple signaling pathways at the basis of cardiac and lung physiopathology. Some of the deleterious effects of Epac, such as cardiomyocyte hypertrophy and arrhythmia, initially described in vitro, have been confirmed in genetically modified mice for Epac1 and Epac2. Similar recent findings have been collected in the lung. The following sections will describe how Epac and cAMP signalosomes in different subcellular compartments may contribute to cardiac and lung diseases.